An Innovative Design by Single‐Layer Superaerophobic Mesh: Continuous Underwater Bubble Antibuoyancy Collection and Transportation. (18th December 2019) - Ning, Yuzhen; Zhang, Di; Ben, Shuang; Zhao, Zhihong; Zha, Jinlong; Tian, Dongliang; Liu, Kesong; Jiang, Lei
Abstract: Underwater bubbles are unavoidable in the natural world and industrial production. Understanding the behavior of underwater bubbles and manipulating gas bubbles are vital important to both fundamental scientific research and industrial application. Although there has been some progress in controlling underwater bubbles, continuous underwater bubble collection and transportation remain challenging targets. Herein, inspired by the mechanism of water spider's gas storage, a strategy to collect and transport underwater gas bubble is demonstrated by design of a single‐layer underwater superaerophobic mesh (USM) assembled with a quartz tube. Gas bubbles supplied by a syringe pump penetrate the mesh pore and then gather to form a gas column in the quartz tube. Collapse occurs when the gas column reach the maximum storage height/pressure. Under a continuous supply of gas bubbles, the change of pressure becomes a cyclic process, which acts in a pump‐like manner to transport bubbles continuously from the water to the gas phase in the USM device assembled with an asymmetric U‐tube. This novel gas collection and transport system provides a new inspiration for developing new technologies for applications in pipes, sensors, gas collection, and environment protection. Abstract : Inspired by the gas storage mechanism of the water spider, a strategy to collect and store underwater gas bubbles is demonstrated based on a single‐layer underwater superaerophobic mesh (USM) assembled with a quartz tube. Moreover, a device with an asymmetrical U‐shaped quartz tube fitted to the USM is designed to realize continuous gas collection and transportation.